Hakikat Pancasila dalam Membentuk Karakter Kebangsaan melalui Organisasi Siswa Intra Sekolah - Damanik, Fritz Hotman (Universitas Negeri Medan, 2014)
As one of the four important guidances in the nation-state life, Pancasila should hopefully being present to accompany the national direction along its experience and struggle of life. However, the reality represents that how Pancasila actually more and more ingored and forgotten by the people instead. Consequently, many problems in turns suffers the nation-state. Such complex of the problems, result in an non-profit organisation centred in Washington named Fund for Peace in June 2012 positioned Indonesia on the rank of 63 of 178 countries in the world in the context of the Lost States Index. Therefore, there is not choice and exception beside to return to Pancasila, seeding it for enhancing in the wholeheart of the youth as the nationâs next mandated generation. Then, in the school context, Studentsâ Organisation of Internal of School (OSIS) for reaching could be used for achieving it.